The mechanics of providence : the workings of ancient Jewish magic and mysticism - Swartz, Michael D. (Texte und Studien zum antiken Judentum, 2018)
"The phenomena we call magic and mysticism had a profound effect on the shaping of Judaism in late antiquity. In this volume, Michael D. Swartz offers a wide-ranging study of the purposes, world-views, ritual dynamics, literary forms, and social settings of ancient Jewish magic and mysticism and their function in religion and history. Based on the author's studies over the past few decades, he proposes innovative methods for the study of these two phenomena. The author focuses especially on the rituals of early Jewish magic and mysticism, their social contexts, and the textual dimension of this complex literature. He also offers introductions to these phenomena. Michael D. Swartz argues that the authors of these texts employed intricate technologies, literary and artistic forms, and physical practices to negotiate between the values and world-views of their cultures and the texture of everyday life."--